Caracterización química preliminar de una muestra de propóleos del cantón Puyango. - Sigüenza Barzallo, Viviana Estefanía (2015)
In the present work a preliminary chemical characterization of a propolis sample from Puyango, employing chromatographic and spectroscopic methods, was realized. Propolis sample was extracted using methanol and the extract was chromatographed over sephadex LH-20 column. The presence of phenolic compounds and triterpenoids was suggested on the basis of TLC analysis and phytochemical screening. Fingerprinting of all sephadex LH-20 fractions was performed using a LTQ-XL ion-trap mass spectrometer (Thermo) equipped with an electrospray ion source. The presence of polar compounds and a quercetin acetate derivative was suggested. All experimental evidences indicated that propolis sample is rich in triterpenes. We suggest continuing the chemical study in order to identify the main compounds present in sephadex fractions unambiguously.